The structure of advertising texts in the newspaper "Kazakh" - Kuderinova Қ.Б.; Mamyrbek Г.М. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The main purpose of the article was to analyze the linguistic specifics of advertising texts in the first national press – the newspaper "Kazakh", organized by the Alash intelligentsia and published in the period from 1913 to 1918. To do this, graphic projections of advertising texts in issues 7-40 of the specified newspaper of 1913 were first created, which were deciphered. A graphic projection is a mechanical marking of a text given by one or another writing system, another alphabet [1, p. 7], without reference to the traditions and writing norms of the copied language, letter and sound content, as well as to the elements that are implicitly transmitted in the original letter. The article also reviewed the history of Kazakh advertising. The structure of sentences, phrases of historical advertising texts in the Kazakh language were analyzed. Based on historical Kazakh advertising texts published in 7-40 issues of the newspaper "Kazakh" in 1913, the types of advertising of the early twentieth century are determined. The meanings of Arabic, Persian words and terms found in the advertising language were revealed. The article found that trade and social advertising was often published in the newspaper "Kazakh", the features of the technology of advertising design of the early twentieth century are described in detail. The article is devoted to the history of the formation of advertising in the Kazakh language.